SPARTACKS: Dinamika Perkembangan Kelompok Suporter Klub Sepakbola Semen Padang FC (2010–2024) - Arda, Azreal Raudhandito; Hardi, Etmi (Lembaga Yasin AlSys, 2025)
The phenomenon of supporter culture in Indonesian football has shown significant development through the emergence of local communities with complex social dynamics. This study examines SPARTACKS (Suporter Padang Anak Rantau Cinta Kabau Sirah), a supporter group of Semen Padang FC, from 2010 to 2024, with the aim of describing the emergence and evolution of this organization and analyzing its impact on the club and surrounding social environment. Using the historical method, which includes heuristic, source criticism, interpretation, and historiography stages, this research constructs a comprehensive narrative based on primary and secondary data, including in-depth interviews, internal documentation, and local and national media coverage, validated through source triangulation. The findings reveal that SPARTACKS serves not only as a supporter group but also as a representation of Minangkabau cultural identity, youth solidarity, and a form of active social expression. Internal and external dynamics, including inter-faction rivalries, conflicts, and organizational transformation, reflect the complex role of this group within the sociocultural context of Padang City. Adaptation to digital technology has further strengthened their presence, although challenges such as the riot incident during the 2024 Liga 2 final remain critical points. This study concludes that SPARTACKS contributes significantly to shaping club identity and enriching the local football atmosphere through structured collective support. Their existence reflects the interaction between local identity, technological development, and socio-political dynamics within the context of modern Indonesian football, affirming their relevance as a subject of urban social history and contemporary sports culture studies.